A comparison of the effects of sheep's milk and cow's milk on recovery from eccentric exercise - Ben Ravenwood; Jane Coad; Matthew J. Barnes (Frontiers Media S.A., 2024)
IntroductionWhen consumed after eccentric exercise, cow's milk has been shown to improve recovery and alleviate symptoms of exercise induced muscle damage. Although currently less commercially available than cow's milk, sheep's milk may offer similar or greater benefits for recovery as it is higher in protein and energy; however, the effect of sheep's milk in any exercise context has not been explored. This study compared the effects of a sheep's milk beverage and a cow's milk beverage on recovery from strenuous eccentric exercise. Additionally, the effects of each beverage on satiety and gastrointestinal comfort were assessed.MethodsTen healthy males completed baseline measures of perceived muscle soreness and maximal voluntary concentric, eccentric, and isometric quadriceps force of one leg before completing 200 maximal eccentric knee extensions on an isokinetic dynamometer. Measures were repeated 0.5, 24, 48 and 72 h post-eccentric exercise. After 0.5 h measures, participants consumed either 450 ml of chocolate flavored sheep's milk or chocolate flavored cow's milk. Following a washout period, participants completed a second trial on the contralateral leg and consumed the other beverage. Additionally, a satiety and gastrointestinal comfort questionnaire was completed before and after each beverage was consumed.ResultsEccentric exercise brought about a significant decrease in muscle function over time (all P < 0.012). No difference between treatments (all P > 0.097) was found. Measures of muscle soreness increased over time (all P < 0.002), however no difference was observed between treatments (all P > 0.072). Only sheep's milk altered perceived satiety, however, only the response to "How full do you feel" differed between treatments (P = 0.04).DiscussionThe results of this study suggest that consuming sheep's milk may provide similar benefits as cow's milk when recovering from exercise-induced muscle damage. While these findings provide initial support for the use of sheep's milk in a muscle recovery context, further research is warranted to confirm these findings. Given its superior nutritional profile, greater impact on satiety and lower environment impact, sheep's milk may be a more efficient post-exercise recovery beverage, compared to cow's milk.